The Application of Compound Interest in Investment Portfolios - Janardana, Komang; Wiriandi, Daffa Ibrahim (International Journal of Quantitative Research and Modeling, 2024)
Effective long-term investment requires a well-structured strategy supported by detailed analysis. The compound interest model serves as a pivotal tool in assessing potential returns on investments by illustrating how interest accumulates on both the initial capital and previously accrued interest. This study delves into the application of compound interest within investment portfolios, aiming to elucidate its impact on long-term growth trajectories. By investigating various factors, such as investment duration and compounding frequency, the research highlights the intricate mechanisms driving investment expansion. A robust understanding of these elements is crucial for making informed financial decisions. The insights gained from this research are intended to equip investors and financial advisors with practical strategies for optimizing portfolio performance and achieving superior investment results, ultimately contributing to the advancement of more sustainable long-term investment practices.